Phosphorylation determines the glucose metabolism reprogramming and tumor-promoting activity of sine oculis homeobox 1 - Yanni Lin; Ling Li; Bin Yuan; Fei Luo; Xiujuan Zhang; Yuanjun Yang; Shaliu Luo; Jing Lin; Tianxing Ye; Youzhi Zhang; Shan Gao; Qinong Ye (Signal Transduction and Targeted Therapy)
Abstract Aerobic glycolysis is a hallmark of cancer and is regulated by growth factors, protein kinases and transcription factors. However, it remains poorly understood how these components interact to regulate aerobic glycolysis coordinately. Here, we show that sine oculis homeobox 1 (SIX1) phosphorylation integrates growth factors (e.g. TGFβ, EGF) to control aerobic glycolysis and determines its tumor-promoting activity. SIX1 is phosphorylated at serine 225 (S225) by growth factors-activated protein kinases ERK1/2 and its phosphorylation is responsible for glycolysis stimulated by some growth factors. SIX1 is dephosphorylated by the atypical protein phosphatase eyes absent 4 (EYA4). Phosphorylation blocks non-canonical ubiquitination and degradation of SIX1 through the E3 ubiquitin ligase FZR1. Unexpectedly, the non-canonical phosphorylation mimic SIX1 (S225K), but not the canonical phosphorylation mimic SIX1 (S225D/E), phenocopies the effects of SIX1 phosphorylation on glycolysis and cancer cell growth and metastasis in vitro and in mice. Compared to normal liver tissues, SIX1 phosphorylation at S225 (pS225) is upregulated in human liver cancer tissues. ERK1/2 expression is positively correlated with pS225 and EYA4 expression is negatively associated with pS225 in liver cancer specimens. Moreover, low expression of pS225 had longer disease-free survival and overall survival in patients with liver cancer. Thus, we identify a common mechanism underlying growth factors-mediated glycolysis, and provide a previously unidentified mode for non-classical phosphorylation mimics of a protein. Targeting growth factors/SIX1 signaling pathway may be beneficial to cancer treatment.